The socioeconomic pattern of health and developmental outcomes among Aboriginal and Torres Strait Islander children - Shepherd, Carrington C J (Curtin University, 2012)
The pervasive health and social disadvantage faced by Aboriginal and Torres Strait Islander peoples is an acknowledged part of Australian society. The contemporary data reveal striking inequalities between Indigenous and non-Indigenous Australians in most measurable aspects of wellbeing across the life cycle. This reflects a postcolonial history of marginalisation and exclusion from mainstream society, dispossession of traditional lands, forced separation from family and kinship networks, and racism. Despite an increased awareness and disapproval of these inequalities in health, the inequalities persist.The lack of progress in the face of public disapproval and progressive government support underscores the fact that we still do not adequately understand the fundamental causes of Indigenous ill health and disease. A small body of research in Australia has highlighted that socioeconomic status (SES) accounts for a portion of the gap in health but this does not imply that they account for health differences within Indigenous population groups. A robust international literature has consistently shown that socioeconomic factors influence population health. These factors reflect the way in which society is ordered according to wealth, prestige, power, social standing or one’s control over economic resources, and their pattern of association with health has almost always depicted better health for those who are better off— that is, the health of population groups normally follows a gradient pattern. Despite the ubiquity of this observation in the empirical literature, there is uncertainty as to whether it applies to Aboriginal and Torres Strait Islander populations in Australia.Accordingly, this thesis has aimed to assess the pattern of socioeconomic disparities in the health and development of Indigenous populations in Australia, with a specific focus on children. The three key objectives were to: • Describe the developmental status of Indigenous children and the mechanisms that influence this status; • Determine the pattern of association between socioeconomic factors and physical and mental health outcomes; and • Reveal the significant differences (and similarities) in the socioeconomic pattern of child health between Indigenous and non-Indigenous populations, and articulate these in terms of their direction, shape and magnitude.The objectives of the study were primarily assessed using a quantitative analytic framework applied to four existing population-representative datasets: the 2008 National Aboriginal and Torres Strait Islander Social Survey, the 2000–2002 Western Australian Aboriginal Child Health Survey, the 2004–05 National Aboriginal and Torres Strait Islander Health Survey and 2004–05 National Health Survey. Simple univariate and cross-tabulation data were used to describe population characteristics, while the relationships between socioeconomic indicators and health outcomes were assessed using a range of regression techniques. Multilevel models are an important feature of this study, and have enabled a more accurate estimation of the effects of individual and area-level measures of SES on health. Generalised Additive Models were used to account for the possible non-linear nature of associations between continuous SES variables and physical health outcomes, with results presented as non-parametric spline curves. The mechanisms linking SES and mental health were explored using a stepwise approach to the regression analysis. All data in all chapters were weighted to reflect population benchmarks.The findings highlighted that there were significant socioeconomic disparities in the health of Indigenous children in Australia, although the direction, shape and magnitude varied, by both socioeconomic measure and health outcome. While the socioeconomic patterns of Indigenous child health are not universal, they are more consistent for mental than physical health. In addition, the thesis has shown that both conventional and alternative notions of SES can influence health patterns. The largest disparities in child physical health were observed for area-level SES indicators, while housing characteristics and area-level SES both had a strong direct effect on child mental health.The thesis has demonstrated that the patterns of socioeconomic disparities in child health differ markedly in Indigenous and non-Indigenous populations—at least in non-remote settings. It was not uncommon for the magnitude of disparity to be larger in the Indigenous population. These findings lend support to the notion that socioeconomic factors have a differential impact on the health of Indigenous and non-Indigenous populations. The implication of this for policy is that a single approach to stimulating socioeconomic conditions will not have equal benefits to child health outcomes in Indigenous and non-Indigenous populations. While the evidence here underscores the validity of the well-worn edict that “one size does not fit all” in Indigenous health policy, it also reinforces the need to examine health disparities within and across Indigenous and other population groups in order to better inform policy and practiceCollectively, the results have provided clear evidence that socioeconomic factors matter to both the physical and mental health of Aboriginal and Torres Strait Islander children. The diversity of findings implies that SES factors are one facet of the unique and complex set of factors that influence Aboriginal child health and wellbeing.This thesis has made several original contributions to the literature on social inequalities in Indigenous health in Australia and the broader field of social determinants of health. It is one of the few studies internationally to explicitly look at the socioeconomic patterning of health in an Indigenous population, and the first to examine these patterns among Indigenous children using population-representative data. In doing so, the study has begun to bridge the knowledge gap on social inequalities in Aboriginal health in Australia, and will facilitate a better grasp of the complex underlying mechanisms that determine Aboriginal health.For policy, this knowledge can lead to more effective government decision-making in terms of targeting social determinants of health that are of particular significance for Aboriginal populations. It is hoped that the findings of the thesis can provide directions for future research and insights to policy that will, ultimately, increase the pace of change toward health equity in Australia.